An unusual case of unilateral vascular hypoplasia in an adult patient – late diagnosis of PHACE syndrome - Regeer, Madelien V.; Stöger, J. Lauran; Bökenkamp, Regina; Lakeman, Inge M.M.; Hazekamp, Mark G.; Kiѐs, Philippine; Egorova, Anastasia D.; Jongbloed, Monique R.M. (International journal of cardiology congenital heart disease, 2023)
A case of unilateral vascular hypoplasia is presented. A female patient was born with a complex aortic arch anatomy - a double aortic arch with an interrupted left arch. Surgical correction was performed at the age of 3 months. The patient was also noted to have had an ipsilateral large infantile haemangioma. These findings raised the suspicion of the diagnosis of PHACE syndrome. PHACE syndrome is an acronym for Posterior fossa abnormalities, Haemangioma, Arterial anomalies, Cardiac anomalies and Eye anomalies. Future research is needed to elucidate the underlying pathophysiology in PHACE syndrome.